2014
DOI: 10.3109/09546634.2014.952610
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of vitiligo with NB-UVB: A systematic review

Abstract: NB-UVB showed equivalent efficacies to UVA, PUVA or 308-nm EL control in the treatment of vitiligo. Side effects of NB-UVB were acceptable. More RCTs were needed to validate the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…It is also discussed that treatment with NB-UVB is more effective and repigmentation is more permanent compared to PUVA. [9][10][11][12][13] In a long-term follow up study, 17 vitiligo patients underwent NB-UVB as monotherapy, and complete remission had been detected in 10 patients at the end of the 1 st year of therapy while mild-to-moderate repigmentation was observed in 2 patients. The best treatment response has been reported in the proximal extremity following the face and neck in cases with vitiligo.…”
Section: Discussionmentioning
confidence: 99%
“…It is also discussed that treatment with NB-UVB is more effective and repigmentation is more permanent compared to PUVA. [9][10][11][12][13] In a long-term follow up study, 17 vitiligo patients underwent NB-UVB as monotherapy, and complete remission had been detected in 10 patients at the end of the 1 st year of therapy while mild-to-moderate repigmentation was observed in 2 patients. The best treatment response has been reported in the proximal extremity following the face and neck in cases with vitiligo.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism behind repigmentation with NB-UVB is not fully understood, it is believed to be caused by a decrease in inflammatory cytokines followed by a stimulation of melanocytes within the hair follicle [ 7 ]. In the treatment of vitiligo, NB-UVB has no significant difference in efficacy compared to PUVA or 308 nm-excimer laser [ 8 ]. A recent retrospective review of 58 patients who received NB-UVB therapy showed persistent skin repigmentation in 80% of patients one year after treatment in those predominantly suffering from non-segmental vitiligo [ 9 ].…”
Section: Reviewmentioning
confidence: 99%
“…A previous study demonstrated that the inhibition of oxidative stress could be an effective therapy for vitiligo ( 6 ). Phototherapy remains the primary vitiligo treatment; using ultraviolet (UV) lamps or lasers, phototherapy helps ameliorate vitiligo through immunosuppression and stimulation of melanocyte generation ( 9 ). The narrow-band (NB)-UVB, a subset of type B ultraviolet light, has emerged as one of the most effective and the safest therapies even for pregnant women and children and it is presently the first choice for clinical treatment of vitiligo ( 10 ).…”
Section: Introductionmentioning
confidence: 99%